PREPARATION AND MODELING OF POTATO POWDER BY THIN LAYER MICROWAVE DRYING - Mishra, Sharmishtha; Kumar, Vivek; Sharma, H K (Potato Journal, 2013)
Microwave roasting and drying of potato were conducted in a domestic microwave oven. Both the experiments were carried out at 180, 360, 540, 720 & 900W. The optimum roasting of potato was found at 900W microwave power level for 3.5 min. Time required for lowering the moisture content of roasted mashed potato from 2.71 to 0.1 on dry basis varied between 6.67 to 37 min at 900W and 180W microwave power level respectively. Seven commonly used mathematical models were evaluated with the experimental data. Page model was found to be most adequate in predicting moisture transfer of roasted mashed potato during microwave drying, followed by Wang & Singh and Logarithmic model. Physico-chemical and functional quality of potato powder prepared by microwave drying at 540W was determined and compared with standard potato flour procured from the market. The physico-chemical quality of the flours was found nearly same but they differ in their functional quality as microwave dried flour having slightly lower value of WAI and Peak viscosity. But the WSI of microwave dried flour was better than standard flour. The hunter colour L* value for microwave dried sample, 73.64 was found to be comparable but slightly lower than the standard market sample, 76.69.